Application of evidence-based recommendations for heat acclimation: Individual and team sport perspectives - Pryor, J. L.; Johnson, E. C.; Roberts, W. O.; Pryor, R. R. (Temperature, 2019)
Heat acclimation or acclimatization (HA) occurs with repeated exposure to heat inducing adaptations that enhance thermoregulatory mechanisms and heat tolerance leading to improved exercise performance in warm-to-hot conditions. HA is an essential heat safety and performance enhancement strategy in preparation for competitions in warm-to-hot conditions for both individual and team sports. Yet, some data indicate HA is an underutilized pre-competition intervention in athletes despite the well-known benefits; possibly due to a lack of practical information provided to athletes and coaches. Therefore, the aim of this review is to provide actionable evidence-based implementation strategies and protocols to induce and sustain HA. We propose the following suggestions to circumvent potential implementation barriers: 1) incorporate multiple induction methods during the initial acclimation period, 2) complete HA 1-3 weeks before competition in the heat to avoid training and logistical conflicts during the taper period, and 3) minimize adaptation decay through intermittent exercise-heat exposure or re-acclimating immediately prior to competition with 2-4 consecutive days of exercise-heat training. Use of these strategies may be desirable or necessary to optimize HA induction and retention around existing training or logistical requirements.